State Interventions Through Regulation: History and Implications—Evidence from the USA, UK, and Pakistan - Fida Muhammad Khan (`, 2025)
Government intervention through Regulation is an Aristotelian concept having deep roots in history. The conflict of market vs. the state has existed in all societies at all times. This paper discusses the history of regulations, with a brief review of Regulations in the USA and UK, and then taking the discussion to Pakistan. The paper concludes that while the intervention of the USA, UK and much of Europe has been surgical here in Pakistan we have had sweeping nationalization programs. The nationalization program has changed the growth trajectory of Pakistan. Had there been no nationalization regimes and the pre - 1970 private sector led growth model had been allowed to evolve, much better results could have been achieved. The paper has used existing knowledge on the hazards of Government interventions in market to advocate market freedom. Keywords: State Interventions, Regulation, History and Implications, USA, UK, Pakistan